Experimental And Finite Element Analyses Of Corrugated Web Steel Beams Subjected To Bending Loads - Chan, Chee Leong (2002)
The behaviour of beams with corrugated web has been investigated throughout this study. They are commonly used in structural steel works to enhance the momentcarrying capability and weight reduction. Experimental tests and finite element analysis were conducted on beams with plane web (PW), horizontally corrugated (HC) and vertically corrugated (VC) webs. Throughout the experimental tests, semicircular shape corrugation of 22.5 mm mean radius and 4.0 mm thickness was used. Two cases were considered for the HC beams, one are (HC 1) and two arcs (HC2) corrugation, while semicircular wholly corrugated was used for the VC type beams. All specimens were fabricated using tubes and flat plates of mild steel material (AlSI 1020). The 1nstron testing machine was used for the three-point bending tests where three tests for each case have been carried out to obtain the load-displacement relations. The plane web I-section beams with the mass per unit length value of 19.3 (kgm-l) was also tested to act as the benchmark result. In the analytical work, finite element models were generated and analysed by using LUSAS software. The material datasets were defined based on the actual stressstrain data obtained from the tensile tests. A series of elastic-plastic nonlinear analysis were carried out with the boundary settings similar to the experiment setup. Three corrugation radii of 22. 50 mm, 33.75 mm and 67.50 mm were considered for the HC beams while five radii, in the range of 11 .25 mm to 33.75 mm for the VC beams. From the results obtained, the VC beams has yield loads of 60.62 1 kN to 73.308 kN or 13.3% to 32.8% higher than the welded plane web beams and 1 .32-1.89 times and 1 .56-3.26 times higher compared to the HCl and HC2 beams respectively. The yield load increases as the larger size of radius was used, which is true for the sizes taken in this study. Moreover, as much as 13.6% of reduction in weight was achieved for the VC beams at the largest value of corrugation radius. A good agreement was found between the experimental and finite element analysis results where the percentage difference obtained was 7.28% to 28.37%.